KONTRIBUSI NILAI TEKNOLOGI INFORMASI TERHADAP KINERJA PROSES BISNIS DAN DINAMIKA BERSAING - EUNIKE KARUNIA SENTOSA (Universitas Katolik Widya Mandala Surabaya, 2012)
In the business world, Information Technology (IT) is a very important role in determining the success of a company. Because, if it is implemented correctly will be able to assist companies in overcoming obstacles and barriers that exist within the company. Therefore, the proper way to find out how the value contribution of IT to business process performance and competitive dynamics is the concept of the value chain. This value chain concept can be used, because the firm must be consist of an activities that related each other. And the concept of value chain helps to see how the value contribution of IT in every activity of the business process. Having known how its contribution to the business process, then it can be seen how the relationship between business processes can affect the competitive dynamics. But the dynamics of competing not only influenced by the support of information technology in every business process, but also influenced by the human resources to manage IT.